PENGARUH MEDIA PEMBELAJARAN INTERAKTIF GAME EDUKASI WORDWALL TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN EKONOMI - Faikotun Nafiah; Putri Ulfa Kamalia (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The low interest in learning Economics among students due to the dominance of conventional worksheets demands innovation in more interactive technology-based learning media. This study aims to test the effect of using the Wordwall educational game on the learning interest of class XI students of SMAN 22 Surabaya. Using a quasi-experimental method with a nonequivalent control group design, this study involved class XI-6 as the experimental group and XI-7 as the control through a saturated sampling technique. The research stages included a pretest, treatment using the Random Wheel and Open the Box features, and a posttest. Quantitative data were analyzed using the Independent Sample T-Test and N-Gain tests. The research findings showed a significant effect of Wordwall on learning interest with a significance value of 0.000 less than 0.05. The learning interest score of the experimental class increased from 72.09% to 84.63% or in the high category, surpassing the control class which only reached 75.64%. The N-Gain test results of the experimental group were 42.18%, which is in the medium category and proved to be much more effective than the control group at 36.79%. Supported by 92.19% observation results, this media was able to create a challenging and participatory learning environment for the students studied. The main conclusion confirms that the integration of the Wordwall educational game effectively optimizes student interest through hands-on learning experiences in accordance with constructivist principles. This innovation serves as a strategic guide for educators in utilizing digital technology to transform the quality of economics learning.